Optimalisasi Potensi Ikan Medai Melalui Pembinaan Pengolahan Bakso Ikan di Kecamatan Gading Rejo, Kota Pasuruan - Roidatus Shofiyah; Hana Wafiqotus Salamah; Siti Lulun Muthoharoh (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
This research was conducted in Gading Rejo District, Pasuruan City, focusing on optimizing the potential of medai fish through training in fish ball production. Data was collected from December 21 to 31, 2024, using methods such as Field Observation, In-Depth Interviews, and Questionnaire Distribution. The results revealed that while the majority of the community (70%) is familiar with fish balls, only a small portion (30%) knows how to make them, and 50% are not aware of the detailed process. This indicates a significant need for practical skills training in processing medai fish into fish balls. This study supports the community empowerment theory, which emphasizes the importance of enhancing practical skills to improve economic competitiveness, as well as the value-added processing theory that encourages creating new business opportunities. Based on these findings, it is recommended that continuous training be conducted to improve the community's knowledge and skills in fish ball production, along with providing facilities to support the production process.